2020
DOI: 10.1111/jan.14327
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of rehospitalization for community‐dwelling older adults with chronic heart failure: A structural equation model

Abstract: Aims:To examine the effects of health literacy, activities of daily living, frailty and self-care on rehospitalization for older adults with chronic heart failure using a structural equation model. Design: This was a cross-sectional study.Methods: Two hundred and seventy-one older patients with chronic heart failure were recruited using a convenience sampling method from three community healthcare centres in Guangzhou, Southern China. The data were collected using a questionnaire survey between April 2018 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
6
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
6
6
0
6
Order By: Relevance
“…[34][35][36][37] Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [38] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [39] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [40] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these findings were similar to the results of our reports on the readmission risk factors for CHF. We found that gender, income, health care, appetite-sleep, anxiety, depression, paranoia, support, and independence were predictors of readmission for CHF.…”
Section: Discussionsupporting
confidence: 80%
“…[34][35][36][37] Kitamura M not only confirmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [38] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [39] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [40] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these findings were similar to the results of our reports on the readmission risk factors for CHF. We found that gender, income, health care, appetite-sleep, anxiety, depression, paranoia, support, and independence were predictors of readmission for CHF.…”
Section: Discussionsupporting
confidence: 80%
“…[39][40][41][42] Kitamura M not only con rmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [43] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [44] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [45] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these ndings were similar to the results of our reports on the readmission risk factors for CHF. We found that gender, income, health care, appetite-sleep, anxiety, depression, paranoia, support, and independence were predictors of readmission for CHF.…”
Section: Discussionsupporting
confidence: 77%
“…[36][37][38][39] Kitamura M not only con rmed that daily activities were independent predictors of readmission in heart failure patients within 90 days, but also calculated the cut-off value by ROC curve [40] and the study have also proved that self-care and daily activities are the mediating factors of readmission of heart failure. [41] While Hochang Benjamin Lee et al emphasized that personality disorders as predictors of incident cardiovascular disease increased risk disease, [42] our results are quite the opposite, which may be because the subjects studied were different; Apart from the results on patient paranoia, these ndings were similar to the results of our reports on the readmission risk factors for CHF. We found that gender, income, health care, appetite-sleep, anxiety, depression, paranoia, support, and independence were predictors of readmission for CHF.…”
Section: Discussionsupporting
confidence: 77%